SAT0609 Venous vessel wall thickness in lower extremity is increased in male behcet's disease patients with and without vascular involvement. (12th June 2018) - Alibaz-Oner, F.; Ergelen, R.; Mutis, A.; Erturk, Z.; Asadov, R.; Ergun, T.; Direskeneli, H.
Abstract : Background: Vascular involvement is seen in up to 40% of the patients with Behcet's Disease (BD), especially in young males and is one of the major causes of mortality and morbidity. Lower extremity vein thrombosis due to vascular inflammation is the most frequent form of vascular involvement in BD. Recently, assessment of vessel wall thickness (VWT) and venous dilatation by US is suggested to be valuable in patients with vascular inflammation. Objectives: In this study, we investigated whether vessel wall thickness or dilatation is present in young male BD patients prone to venous vascular disease. Methods: Thirthy male patients with BD without major organ involvement and 29 male patients with Vascular BD(VBD) followed in Marmara University Behcet's Clinics, 24 healthy male controls and 27 male patients with Ankylosing Spondylitis (AS) were included the study. Bilateral lower extremity venous doppler ultrasonography (US) was performed by an experienced radiologist blinded to cases. No patients except VBD were under immunosuppressive treatment. Bilateral common femoral vein (CFV) wall thickness and great/small saphenous vein dilatations were examined. Behçet Syndrome Activity Score (BSAS) was used for the general assessment of disease activity. In 10 patients, CFV wall thickness was measured by 2 different radiologist (RE, RA) in the same day to calculate "inter-observer reliability". Correlation between radiologists was good. (r=0.765, p<0.001). Results: The mean disease duration was 9.1±6 years in patients with BD. BSAS score was 24±17. All venous measurements were significantly higher in BD compared to AS and healthy controls (p<0.001 for all, table 1). When we compared mucucutaneous BD and VBD, all measurements of patients with VBD were higher than mucocutaneous BD. But only left CFV thickness and width of right great saphenous vein reached the statistical significance (p<0.001, an p=0.028, respectively, figure 1). There were no correlations between BSAS, acute phase reactants and venous wall measurements. Conclusions: In our study, an increased venous vessel wall thickness in lower extremity was shown in male BD patients with or without vascular involvement. As a similar change was not observed in controls, we think, increased VWT might be an early sign of venous inflammation in patients with BD rather than a result of non-specific systemic inflammation. Disclosure of Interest: None declared